2015
DOI: 10.1038/srep11540
|View full text |Cite
|
Sign up to set email alerts
|

Detection of highly conductive surface electron states in topological crystalline insulators Pb1−xSnxSe using laser terahertz radiation

Abstract: We suggest a method for detection of highly conductive surface electron states including topological ones. The method is based on measurements of the photoelectromagnetic effect using terahertz laser pulses. In contrast to conventional transport measurements, the method is not sensitive to the bulk conductivity. The method is demonstrated on an example of topological crystalline insulators Pb1−xSnxSe. It is shown that highly conductive surface electron states are present in Pb1−xSnxSe both in the inverse and d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…There have been many theoretical and experimental works in the past few years on helicity-controlled photocurrents [14][15][16][17][18], the linear photogalvanic effect [19][20][21], local photocurrents [22,23], edge photocurrents in two-dimensional (2D) TIs [24,25], coherent control of injection currents [26,27], photon drag currents [19,28,29], second-harmonic generation [30], photoinduced quantum Hall insulators [31,32], cyclotron-resonance-assisted photocurrents [33,34], quantum oscillations of photocurrents [35], photogalvanic currents via proximity interactions with magnetic materials [36][37][38], and the photoelectromagnetic effect [39]. These phenomena, scaling in the second or third order of the radiation electric fields, open up new opportunities to study Dirac fermions, which has been already demonstrated for graphene (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…There have been many theoretical and experimental works in the past few years on helicity-controlled photocurrents [14][15][16][17][18], the linear photogalvanic effect [19][20][21], local photocurrents [22,23], edge photocurrents in two-dimensional (2D) TIs [24,25], coherent control of injection currents [26,27], photon drag currents [19,28,29], second-harmonic generation [30], photoinduced quantum Hall insulators [31,32], cyclotron-resonance-assisted photocurrents [33,34], quantum oscillations of photocurrents [35], photogalvanic currents via proximity interactions with magnetic materials [36][37][38], and the photoelectromagnetic effect [39]. These phenomena, scaling in the second or third order of the radiation electric fields, open up new opportunities to study Dirac fermions, which has been already demonstrated for graphene (for a review see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recently the second approach was used to demonstrate existence of highly conductive surface electron states in Pb Sn Se alloys through measurements of the photoelectromagnetic effect induced by terahertz laser radiation pulses [15]. These direct-gap semiconductors are classified as topological crystalline insulators (TCIs) at , where the energy spectrum is inverted [4], [5], [16].…”
Section: Introductionmentioning
confidence: 99%
“…At lower tin contents , the alloys possess a normal sequence of energy bands which should prevent formation of topological surface electron states. On the other hand, experiments performed in [15] have demonstrated that highly conductive surface electron states are present in Pb…”
Section: Introductionmentioning
confidence: 99%
“…Lead chalcogenides and Pb 1−x Sn x Te(Se) solid solutions pass to the TCI phase at certain values of the concentration of tin when the inversion of bands of different parities occurs at the L points [54][55][56][57]. The role of spatial symmetry in these compounds is played by mirror symmetry, which persists not for any orientations of the surface.…”
Section: Topological Surface Statesmentioning
confidence: 99%